PENERAPAN PELAKSANAAN ASESMEN TERHADAP PECANDU DAN KORBAN PENYALAHGUNAAN NARKOTIKA DI KEPOLISIAN RESORT SIAK - Bayu saputra simanjuntak; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The current misuse and trafficking of Narcotics has reached a level that is alarming and threatens all aspects of the life of the nation and state. Based on data obtained from the Siak Resort Police from 2017 to 2019, there were 438 suspects of Narcotics abuse, all of the suspects were sentenced to imprisonment. Prison punishment is still the main law enforcement choice compared to rehabilitation measures. Basically the sanctions stipulated in Law Number 35 of 2009 concerning Narcotics adhere to a double track system, namely in the form of criminal sanctions and action sanctions. Rehabilitation is a form of sanction for action. The assessment process is very important to be carried out so that victims of drug abusers and addicts receive rehabilitation.This study uses a typology of empirical legal research or sociological legal research. This study aims to determine the extent to which the law works in society. In this study the authors used the nature of qualitative research, because the authors compared the incidents in the field using existing statistics or data, especially in the implementation of the assessment of addicts and victims of drug abusers.The results of the research conducted by the author are related to the implementation of the assessment of victims of abusers and narcotics addicts in Siak Regency, it can be said that it has not run optimally. There are also several obstacles, such as differences in the perspective of law enforcement officials and the substance that regulates the assessment is still not optimal. In addition, efforts that can be made by law enforcement officials include equalizing perceptions of the assessment itself, increasing good communication and being active in socializing the importance of assessment.Keywords: Narcotics - Implementation - Assessment